2019
DOI: 10.1186/s13756-019-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to the successful introduction of an electronic hand hygiene monitoring system, a cohort observational study

Abstract: Background Hand hygiene (HH) compliance remains low in many intensive care units (ICU). Technology has been suggested to improve HH compliance. We describe the introduction of an electronic HH surveillance and intervention system into the general ICU of a tertiary care teaching hospital, the obstacles to success and reasons for the system’s ultimate failure and removal. Methods The system was based on radiofrequency transmitters in patient areas, on HH disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…[10][11][12][13] Automated hand hygiene monitoring systems (AHHMSs) are increasingly common, [14][15][16] but they have varying accuracy. 9,[17][18][19][20][21][22][23] Some AHHMSs record the use of alcohol-based hand rub (ABHR) and soap, while others record the number of times dispensers are used and compare that to an estimated number of hand hygiene opportunities. 24 These systems can accurately estimate an aggregate adherence rate for a hospital, unit, or individual room within a hospital, but they cannot distinguish between healthcare worker (HCW) types or provide individualized HCW data.…”
mentioning
confidence: 99%
“…[10][11][12][13] Automated hand hygiene monitoring systems (AHHMSs) are increasingly common, [14][15][16] but they have varying accuracy. 9,[17][18][19][20][21][22][23] Some AHHMSs record the use of alcohol-based hand rub (ABHR) and soap, while others record the number of times dispensers are used and compare that to an estimated number of hand hygiene opportunities. 24 These systems can accurately estimate an aggregate adherence rate for a hospital, unit, or individual room within a hospital, but they cannot distinguish between healthcare worker (HCW) types or provide individualized HCW data.…”
mentioning
confidence: 99%
“…All the 89 reviewed studies were published between 2009 and 2020, with 9 (10%) dated in or before 2010 [ 42 , 46 , 56 , 60 , 81 , 83 , 86 , 92 , 113 ], 38 (43%) dated between 2011 and 2015 [ 32 , 33 , 36 , 38 , 39 , 45 , 48 , 49 , 51 , 52 , 54 , 59 , 61 , 63 - 65 , 67 , 68 , 72 , 73 , 78 - 80 , 82 , 84 , 87 - 89 , 93 - 97 , 99 - 101 , 108 , 116 ], and 42 (47%) dated in or after 2016 [ 25 , 29 - 31 , 34 , 35 , 37 , 40 , 41 , 43 , 44 , 47 , 50 , 53 , 55 , 57 , 58 , 62 , 66 , 69 - 71 , 74 - 77 , 85 , 90 , 91 , 98 , 102 -…”
Section: Resultsmentioning
confidence: 99%
“…Of the 32 studies, 10 (31%) developed or deployed an RFID-based RTLS [ 71 , 73 , 75 , 76 , 83 , 84 , 90 , 93 , 97 , 99 ]. RFID uses radio waves to identify and track tags attached to objects.…”
Section: Resultsmentioning
confidence: 99%
“…Vaisman A et al [ 25 ] found that the number of HHEs recorded by EHHMS was 2.5 times higher when the observer was present than absent, and the difference may be attributed to the Hawthorne effect. Besides, the EHHMS was not as accurate as of the direct observation method in the identification of HH indicators [ 26 ], so more HH moments were recorded [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, EHHMS also has some limitations [ 12 , 16 , 26 ], such as the inability to monitor the correctness of HH, which usually costs a lot, and the failure to follow the five HH moments recommended by WHO adequately. The type2 system in this study, like many systems [ 24 , 28 ], can only detect 1, 4, and 5 of the five WHO’s HH moments, but not 2 and 3.…”
Section: Discussionmentioning
confidence: 99%